2011
DOI: 10.1590/s0101-20612011000200037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pectinolitic enzymes on the physical properties of caja-manga (Spondias cytherea Sonn.) pulp

Abstract: Effect of pectinolitic enzymes on the physical properties of caja-manga (Spondias cytherea Sonn.) pulp Efeito de enzimas pectinolíticas nas propriedades físicas da polpa de cajá-manga (Spondias cytherea Sonn.)Marcelo Andres UMSzA-GUez 1 *, Rebeca RINAldI 1 , ellen Silva lAGo-VANzelA 1 , Natalia MARTIN 2 , Roberto da SIlVA 3 , eleni GoMeS 4 , João Cláudio ThoMéo 1 IntroductionBrazil is the third largest world producer of fresh fruit, harvesting about 42 million tons per year (Food..., 2009). Nonetheless, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…However, it was undesirable to liquefy puree with too much heat and longer time as it would cause unfavorable cooked off‐flavor and destructive effect on the enzyme activity (Umsza‐Guez et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it was undesirable to liquefy puree with too much heat and longer time as it would cause unfavorable cooked off‐flavor and destructive effect on the enzyme activity (Umsza‐Guez et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…; Umsza‐Guez et al . ) before viscosity measurement. The study on the effect of incubating time and temperature on puree was conducted by using the obtained best enzyme concentrations (combination of Pectinex Ultra SP‐L and Celluclast 1.5 L, 0.5% [v/w] each) as fix variable for treatments at varying time and temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Through the obtained Pareto graph, it was observed that the variables time and enzymatic concentration (within the studied values) were those that had a significant effe t 5% o the pulp s lu i osity. U szaGuez et al 24 verified that the period of exposure to pectinolytic enzyme results in the increase of L* values. This was also found by Sin et al 29 in the clarification of sapodilla juice.…”
Section: Resultsmentioning
confidence: 95%
“…UMSZA-GUEZ et al 24 verified that the viscosity of the pulp of the caja-manga fruit is directly affected by the time and pectinolytic enzyme concentration, the study recommended ranges of the variables enzyme concentration, process temperature and incubation time, respectively, 0.042-0.068%, 47.0-49.0 ºC and 82-90 minutes. LEE et al 25 Kaur and Sharma 9 applied the pectinolytic enzyme in carrot juice and verified the decrease in viscosity in the juice after treatment in the established conditions.…”
Section: Resultsmentioning
confidence: 96%
“…colloidal polysaccharide particles in juices [49].A juice that is to be marketed as clear should have no turbidity or no unstable cloud which is considered ''muddy'', otherwise it will not be acceptable to be marketed [50]. The decrease in turbidity on increasing pectinase concentration was also reported by Alam et al [43] for carrot juice, Karangwa et al [51] for blended carrot-orange juice, Vinjamuri and Bhavikatti [52] for mixed fruit juices, Umsza-Guez et al [53] for caja-manga pulp, Abdullah et al [54] for carambola fruit juice and Sin et al [55] for sapodilla juice. The effect of experimental variables (Pectinase enzyme concentration and incubation time) on papaya juice turbidity is shown in Fig 8 as response surface and contour plots generated from fitted model.…”
Section: Turbiditymentioning
confidence: 84%